Using guidelines to improve neonatal health in China and Vietnam: a qualitative study - Joanna Raven; Xiaoyun Liu; Dan Hu; Weiming Zhu; Dinh Thi Phuong Hoa; Le Minh Thi; Doan Thi Thuy Duong; Alvaro Alonso-Garbayo; Tim Martineau (BMC, 2016)
Abstract Background Neonatal health (NH) remains a major problem in many countries. Children dying before 28 days often suffer from conditions that are preventable or treatable with proven, cost-effective interventions. The knowledge gaps are no longer about what should be done, but to understand why guidelines including these interventions are not followed. Using a behaviour change framework, this study explores neonatal health guidelines use and the role of management in supporting effective usage in two rural settings in China and Vietnam. Methods Semi-structured interviews with policy makers, health care managers and providers (n = 49) and focus group discussions with women, husbands and grandmothers who had experienced maternal and NH care services within the last year (n = 7) were conducted. Data were analysed using the framework approach. Results Guidelines are not readily available at county, township and village levels in the study sites in China, whereas, in Vietnam, guidelines are available, accepted and being used at facility level. Improvements in implementation could be made in both settings. Factors influencing guidelines use common to both settings included: lack of equipment and supplies; shortage of staff with NH care experience; and guidelines not in line with patient practices. Factors specific to China included: poor guidelines dissemination; and disagreement with guidelines. There was limited community engagement in NH services in China, whereas in Vietnam, community members were actively involved in decision making and provision of services. Managers have an important role in supporting NH guidelines use through: ensuring guidelines are available; allocating appropriate resources; supporting and monitoring staff in their use; and engaging with local communities to promote effective practices. Conclusions Engaging managers to support implementation is crucial. Management systems that provide the necessary resources, competent staff, and monitoring, regulatory and incentive frameworks as well as community engagement are needed to promote adoption of guidelines. Further research on how best to strengthen local level management so that they tailor interventions to support guideline use to their specific context is needed. This will ensure that proven interventions to address NH problems are used, and that countries move closer to achieving the new Sustainable Development Goal 3 target.